REMOVAL OF COPPER ION FROM WASTEWATER BY FLOTATION (Journal of Engineering, 2011)
Several industrial wastewater streams may contain heavy metal ions, which must be effectively removalbefore the discharge or reuse of treated waters could take place. In this paper, the removal of copper( II)by foam flotation from dilute aqueous solutions was investigated at laboratory scale. The effects ofvarious parameters such as pH, collector and frother concentrations, initial copper concentration, air flowrate, hole diameter of the gas distributor, and NaCl addition were tested in a bubble column of 6 cm insidediameter and 120 cm height. Sodium dodecylsulfate (SDS) and Hexadecyl trimethyl ammonium bromide(HTAB) were used as anionic and cationic surfactant, respectively. Ethanol was used as frothers and theoptimal removal conditions have been established. Successful removals about (98%) and (76%) could beachieved for copper ions with SDS and HTAB, respectively. Copper removal reached about 80% underthe optimum conditions at low pH; at high pH it became as high as 98% probably due to the contributionfrom the flotation of precipitated copper. It was found that the presence of NaCl in the solution reducedthe recoveries. Adding ethanol at 1% concentration increased the removal efficiency. From the results therate of flotation was found to be first order.